Coupled Enzymatic Treatment and Mass Spectrometric Analysis for Identification of Glucuronidated Metabolites in Human Samples. (8th May 2019) - Correia, Mario S. P.; Rao, Menghua; Ballet, Caroline; Globisch, Daniel
Abstract: Glucuronidation is the most common phase II modification and plays an important role in human clearance metabolism. Glucuronidated metabolites have also been linked to disease development and microbiota–host co‐metabolism. Although many of these compounds have been identified, the total number of unknown glucuronides and their impact on the human host's physiology can only be estimated. Herein, we describe the combination of an untargeted metabolomics analysis and enzymatic metabolic conversion for the selective detection of glucuronide conjugates by using UPLC‐MS/MS in human urine samples. Our study demonstrates that this powerful strategy can be used for the selective identification of glucuronidated molecules and to discover unknown natural metabolites. In total, we identified 191 metabolites in a single sample including microbiota‐derived compounds as well as previously unidentified molecules. Abstract : Breaking better : A new mass spectrometric method has been coupled with enzymatic metabolite conversion for the selective analysis of glucuronidated molecules. This tailored analysis led to the identification of previously unknown metabolites in the human body.